Hak-hak perempuan dalam Islam - Naila Farah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
Today's women's issues are still very important to pay attention to because women's rights have not been fully fulfilled. The marginalization of women's rights often stems from local religious and cultural beliefs. This is where the importance of the thinking of figures like Asghar Ali Engineer is reviewed in the present. This paper discusses the thoughts of Asghar Ali Engineer about liberation theology in the matter of women's rights in Islam. Asghar Ali Engineer in many of his works has offered various kinds of deconstruction of discourses. In the matter of women's rights in Islam, he presents his opinion on inheritance, wealth, testimony, the position of women in the family, polygamy and divorce which are considered as examples of inequality. With its hermeneutic interpretation, Asghar Engineering rejects the existence of a patriarchal concept that is inherent in the classical interpretation of the Quran, which is considered discriminatory against women. Then he applies the verses of the Quran into two, namely normative and contextual, with the hope that the verses of the Quran can be reinterpreted, so that it truly becomes a universal verses of â€œdas solenâ€ on one side and contextual verses of â€œdas seinâ€ on the other. Thus, the equality of men and women can be realized and gender-based justice can be manifested.